2021
DOI: 10.21608/ejchem.2021.64760.3386
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of new 1,2,4-triazole anticancer scaffold derivatives: In Vitro study

Abstract: Four Schiff bases were obtained via one direct click reaction between 3-amino-1H-1,2,4-triazole and different substituted benzaldehyde. The synthesized compounds were characterized on the basis of their spectral data including IR spectra, mass spectroscopy and 1 HNMR. The synthesized compounds were tested against three human cancer cell lines to evaluate their in vitro anticancer activity, and also tested on Vero cells extracted from African green monkey kidney to investigate their side effect. The screening s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…According to previous studies, which revealed that coumarin, chalcone fibrates can down-regulate the total cholesterol (TC), phospholipids (PL) and triglycerides (TG) and regulate the levels of VLDL, LDL, and HDL, on the other side, pyrimidine serves an essential function in human proliferation as ribonucleotide bases in RNA and as deoxyribonucleotide bases in DNA, and it has been found to contribute to multiply biological activates (7). They are considered powerful tools for treatments and possess broad, interesting biological activities such as anti-tumor and anti-fungal and they are used for thyoid drugs and leukemia (8).…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies, which revealed that coumarin, chalcone fibrates can down-regulate the total cholesterol (TC), phospholipids (PL) and triglycerides (TG) and regulate the levels of VLDL, LDL, and HDL, on the other side, pyrimidine serves an essential function in human proliferation as ribonucleotide bases in RNA and as deoxyribonucleotide bases in DNA, and it has been found to contribute to multiply biological activates (7). They are considered powerful tools for treatments and possess broad, interesting biological activities such as anti-tumor and anti-fungal and they are used for thyoid drugs and leukemia (8).…”
Section: Introductionmentioning
confidence: 99%